A hall sensor packaging process for eliminating packaging stress

CN122995518APending Publication Date: 2026-10-27NANJING TOKEN ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611184285.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0028]1、通过在霍尔IC表面及周边涂覆柔性应力隔离涂层,形成弹性模量为MPa级的应力缓冲垫,吸收灌封料固化收缩和热膨胀应力,使传递至霍尔IC的残余应力大幅衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995518A_ABST
    Figure CN122995518A_ABST
Patent Text Reader

Abstract

The application relates to a Hall sensor packaging process for eliminating packaging stress, and belongs to the technical field of Hall sensor packaging. After PCB welding, a flexible stress isolation coating is first coated on the surface and periphery of a Hall IC packaging body and is pre-solidified, then the PCB is loaded into a sensor plastic shell, the whole is preheated to 5-10 DEG C above the glass transition temperature of the pouring sealing material, the epoxy pouring sealing material is injected, and after heat preservation and solidification, the temperature is reduced to room temperature at a controlled rate of 0.5-1.5 DEG C / min. Through the cooperation of the two mechanisms of local flexible stress isolation and global heat pre-compression cooling, the packaging stress generated by the solidification shrinkage of the pouring sealing material and the thermal expansion mismatch of multiple materials is eliminated, and low-stress packaging in the whole temperature range is realized. Experimental results show that the output temperature drift of the sensor packaged by the process is reduced from + / -18 mV to + / -7 mV, and the reduction is about 61% compared with the traditional process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of Hall sensor packaging technology, and specifically relates to a Hall sensor packaging process that eliminates packaging stress. Background Technology

[0002] Hall effect sensors, as core components for power detection, are widely used in servo motor drives, frequency converters, welding machines, uninterruptible power supplies, electric vehicles, electric locomotives, and automatic monitoring of power grids. A typical module-level packaging process is as follows: purchasing pre-packaged Hall effect ICs → SMT reflow soldering onto the PCB → encapsulation in a plastic housing → injection of epoxy potting compound and heat curing → completion of encapsulation. After curing, the epoxy potting compound completely encapsulates the PCB and all components, providing electrical insulation, mechanical fixation, and protection.

[0003] The existing process has the following technical problems:

[0004] First, there is the curing shrinkage stress of the potting compound: the chemical shrinkage rate of epoxy potting compound during curing is 1.5%~2.5%, and the shrinkage stress directly acts on the surface of the Hall IC mold and the pin solder joints, resulting in zero-point drift and a decrease in linearity.

[0005] Second, thermal stress caused by the mismatch of the coefficient of thermal expansion (CTE) of multiple materials: there are orders of magnitude differences in the thermal expansion of the shell, potting compound, PCB substrate and Hall IC molding compound, which generate alternating thermal stress during temperature cycling, leading to fatigue cracking of solder joints and debonding of the potting compound-shell interface after long-term service.

[0006] Thirdly, there are shortcomings in existing technologies: CN110718509A (Zhuhai Gree Electric Appliances Co., Ltd.) proposes to set a polyimide stress buffer layer between the bare chip of electronic components and the plastic encapsulation protective layer. However, this solution is for the one-time plastic encapsulation process at the bare die level of the chip, rather than the module-level shell potting process after the finished Hall IC is soldered to the PCB by SMT, which is the target of this solution. The two are fundamentally different in terms of packaging level (chip level vs. module level), stress source (mold injection pressure vs. chemical shrinkage of potting material + multi-material CTE mismatch) and process parameters. This solution also does not involve the stress relief method of establishing a compressive prestress field through preheating and controlled cooling. CN114388692B (Chizhou Huayu Electronics) proposes a solution combining dispensing and shaping with three-stage isothermal curing to release chip molding stress. However, its technical solution only involves optimizing the curing process parameters at the bare die level, using a single isothermal segmented curing method to release stress. It does not form a local flexible stress isolation layer covering the finished IC package, nor does it involve a stress relief method that preheats the shell and PCB as a whole to above the Tg of the potting material and then cools it in a controlled manner to establish a compressive pre-stress field after the shell is potted. CN110808236B (Ningbo CRRC Times Sensing) proposes PCB slotting to expose the chip surface to release internal stress. This solution passively avoids stress caused by the potting material wrapping the chip through structural design. This is different from the active stress relief route of this invention, which actively establishes a flexible isolation layer on the IC surface and uses thermal means to establish a compensating pre-stress field. Furthermore, it is not applicable to module-level potting of already packaged Hall ICs. Furthermore, the industry-standard segmented curing and furnace cooling process only aims to degas and level the material during preheating. It does not use the glass transition temperature (Tg) of the potting compound as a reference to precisely set the preheating temperature in order to actively create compressive prestress to offset the thermal expansion tensile stress.

[0007] In summary, there is an urgent need to provide a Hall sensor packaging process that eliminates packaging stress. Summary of the Invention

[0008] The purpose of this invention is to provide a Hall sensor packaging process that eliminates packaging stress, thereby solving the problem of Hall IC output drift and long-term reliability degradation caused by the curing shrinkage of potting material and CTE mismatch of multiple materials in the existing module-level housing potting process.

[0009] The technical solution of the present invention is as follows:

[0010] A Hall sensor packaging process for eliminating packaging stress includes the following steps:

[0011] S1: PCB soldering: Using SMT reflow soldering process, Hall IC and other electronic components are soldered onto the corresponding pads on the PCB, and then allowed to cool naturally to room temperature after soldering;

[0012] S2: Application of flexible stress isolation coating: Apply a layer of flexible stress isolation coating material to the surface of the Hall IC package and its surrounding area on the PCB that has been soldered.

[0013] S3: Pre-curing of flexible stress isolation coating: Pre-cur the coated PCB at 60~80℃ for 30~60min to allow the flexible coating to reach initial shape;

[0014] S4: PCB installation into the housing: The pre-cured PCB is installed and positioned inside the sensor's plastic housing;

[0015] S5: Preheat the entire shell to a temperature above Tg of the epoxy potting compound: Place the entire shell into a temperature-controlled oven and heat it at 2~3℃ / min to the preheating temperature Tp=Tg+ΔT, where Tg is the glass transition temperature of the epoxy potting compound, ΔT=5~10℃, and maintain the temperature for 15~30min.

[0016] S6: Potting at preheated temperature: Keep the oven temperature constant at Tp and inject epoxy potting compound into the shell to the filling height;

[0017] S7: Thermal curing: Complete the full curing of epoxy potting compound under the set segmented curing temperature curve;

[0018] S8: Controlled slow cooling: After curing, the temperature is slowly reduced from the curing temperature to 25±5℃ at a controlled cooling rate of 0.5~1.5℃ / min.

[0019] Furthermore, the flexible stress isolation coating material mentioned in step S2 is a low-modulus electrical insulating material with a Shore A hardness of 30-50 and an elastic modulus in the range of 0.5-5 MPa, and the ratio of its elastic modulus after curing to the elastic modulus of the epoxy potting compound mentioned in step S6 after curing is ≤1 / 100.

[0020] Furthermore, the flexible stress isolation coating material is a two-component addition-type silicone gel, wherein component A1 is the base component, containing vinyl-terminated polydimethylsiloxane and a platinum catalyst, and component B1 is the crosslinking component, containing a hydrogen-containing silicone oil crosslinking agent and an inhibitor. Components A1 and B1 are mixed in a mass ratio of 10:1.

[0021] Furthermore, the flexible stress isolation coating material is one of a single-component condensation-type room temperature vulcanizing silicone rubber, a two-component polyurethane elastomer, or a modified silicone gel.

[0022] Furthermore, the coating thickness of the flexible stress isolation coating in step S2 is 1.0 ± 0.1 mm.

[0023] Furthermore, before applying the flexible stress isolation coating, step S2 also includes an ion activation treatment of the soldered PCB: the PCB is placed in the vacuum chamber of a plasma cleaner, high-purity argon gas is introduced, and the PCB is treated for 60 seconds at a working pressure of 50~80 Pa and a radio frequency power of 200W.

[0024] Furthermore, the epoxy potting compound described in step S6 is a two-component epoxy system, wherein component A2 is a mixture of bisphenol A type epoxy resin and spherical alumina filler, wherein the spherical alumina filler accounts for 60% of the total mass of component A2, and component B2 is methyltetrahydrophthalic anhydride curing agent, with A2:B2=100:80.

[0025] Furthermore, the segmented curing in step S7 includes: first, maintaining a constant temperature of 125°C for 2.0 hours to complete gel pre-curing, and then increasing the temperature to 145°C at a rate of 1.5°C / min and maintaining the temperature for 3.0 hours to complete curing.

[0026] Furthermore, after the pre-curing is completed in step S3, the Shore A hardness of the flexible stress isolation coating reaches 60% to 80% of its fully cured target value.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] 1. By coating the surface and surrounding area of ​​the Hall IC with a flexible stress isolation coating, a stress buffer pad with an elastic modulus of MPa is formed, which absorbs the stress from the curing shrinkage and thermal expansion of the potting compound, thus significantly reducing the residual stress transmitted to the Hall IC.

[0029] 2. By preheating the shell and PCB to 5~10°C above the potting compound Tg and then potting and cooling them at a controlled rate after curing, a compressive prestress field is established by utilizing the gradient shrinkage of the high CTE of the shell and the CTE of the potting compound. The direction of this prestress is opposite to the direction of the tensile stress generated by the temperature rise during use, and after offsetting, the net stress of the Hall IC is significantly reduced.

[0030] 3. The sensor packaged using this process exhibits a reduced full-temperature range output temperature drift of ±7mV compared to the traditional one-time curing process, from ±18mV. After 500 cycles within the range of -40℃ to 125℃, the zero-point drift decreases from 7.5mV to 1.0mV (a reduction of approximately 87%). In summary, this invention, through a combination of local flexible isolation and global thermal pre-compression, simultaneously improves the initial temperature drift characteristics and long-term thermal cycling reliability of the sensor module, achieving effective control of packaging stress throughout the sensor's entire lifespan. Attached Figure Description

[0031] Figure 1 This is a complete flowchart of the packaging process of the present invention;

[0032] Figure 2The temperature-time curves for steps S5 to S8 are shown below.

[0033] Figure 3 This is a comparison curve of sensor output temperature drift between the embodiments and comparative examples of the present invention. Detailed Implementation

[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] like Figure 1-3 As shown, a Hall sensor packaging process for eliminating packaging stress includes the following:

[0036] Sensor module basic information: Open-loop Hall current sensor, rated measurement current 100A. Housing material is PBT reinforced with 30% glass fiber, heat distortion temperature 215℃, CTE approximately 65 ppm / ℃. PCB material FR-4, board thickness 1.6mm. Hall IC is an SOP packaged finished chip, CTE approximately 10 ppm / ℃.

[0037] S1: PCB soldering

[0038] All components were soldered using standard SMT reflow soldering technology. The peak reflow temperature was 245℃, and the time above the liquidus was 60~90s. After soldering, an automated optical inspection device confirmed that each solder joint was free of bridging, cold solder joints, and insufficient solder. The PCB was then allowed to cool naturally to room temperature (25±5℃) via a conveyor belt.

[0039] S2: Application of flexible stress isolation coating

[0040] S2-1: Surface pretreatment before coating. The PCB is placed in the vacuum chamber of a plasma cleaner, and high-purity argon gas is introduced. It is treated for 60 seconds at a working pressure of 50~80 Pa and a radio frequency power of 200W. After plasma activation treatment, organic contaminants adsorbed on the PCB solder mask layer and IC molding compound surface are removed and polar functional groups (such as -OH, -COOH) are introduced to improve coating adhesion.

[0041] S2-2: Coating Material Preparation. A two-component addition-type room temperature vulcanizing silicone gel is selected. Component A1 is the base component, containing vinyl-terminated polydimethylsiloxane and a platinum catalyst. Component B1 is the crosslinking component, containing a hydrogen-containing silicone oil crosslinking agent and an inhibitor. Components A1 and B1 are mixed in a mass ratio of 10:1. During use, the platinum catalyst catalyzes the hydrosilylation reaction between the Si-H bonds in the hydrogen-containing silicone oil and the C=C bonds in the vinyl silicone oil, resulting in crosslinking and curing into an elastomer. The platinum catalyst is a Karstedt catalyst (platinum-divinyltetramethyldisiloxane complex) or an alcoholic solution of chloroplatinic acid.

[0042] Components A1 and B1 are vacuum degassed separately and then injected into a two-component dispensing machine. After being uniformly mixed through a 24-section static mixing tube, they are extruded. The cured coating material has a Shore A hardness of 40, an elastic modulus of 2 MPa, an elongation at break of 350%, and a volume resistivity of 2 × 10⁻⁶. 15 Ω·cm, insulation strength ≥15 kV / mm, is an electrical insulating material. Its coating on the Hall IC pins and solder joints does not affect the metal solder interconnection formed between each pin and the PCB pad. Its high insulation can further enhance the electrical isolation between the pins. Operating temperature range: -60℃ to 200℃.

[0043] It is understood that the flexible stress-isolating coating material is not limited to the aforementioned two-component addition-type silicone gel. In other optional embodiments, low-modulus electrical insulating materials with a Shore A hardness of 30-50 and an elastic modulus of 0.5-5 MPa, such as one-component condensation-type room temperature vulcanizing silicone rubber, two-component polyurethane elastomer, or modified silicone gel, can also be used. As long as the ratio of the elastic modulus after curing to that after curing of the epoxy potting compound is ≤1 / 100, the stress buffering effect can be achieved.

[0044] S2-3: Coating process. The PCB pre-treated in step S2-1 is fixed on the working platform of the automatic dispensing machine. The machine vision system automatically generates the coating path after recognizing the position and orientation of the Hall IC.

[0045] Dispensing parameters: needle inner diameter 0.41mm, dispensing pressure 0.15 MPa, moving speed 8 mm / s. A two-coat overlay method is used: the first coating thickness is 0.5~0.6mm, allowed to stand for 5 minutes to level; the second coating thickness is 0.4~0.5mm, for a total thickness of 1.0±0.1mm. The coating area covers the top surface of the Hall IC package, all four sides, all pin lead-out sections, and solder joint areas, with a boundary 6mm from the edge of the IC package. Coating environment conditions: temperature 22~28℃, relative humidity 30~60%.

[0046] S2-4: Vacuum Degassing. After coating, place the PCB in a vacuum chamber and evacuate to ≤50 mbar for 5 minutes to eliminate air bubbles trapped inside the coating. After degassing, inspect the coated area with a 10x magnifying glass to confirm that no air bubbles larger than 0.1 mm in diameter remain. After coating, use a multimeter or probe tester to randomly check the continuity between each pin and the PCB pads to ensure that the flexible coating does not create open circuits in the soldered interconnects.

[0047] S3: Pre-curing of flexible stress isolation coating

[0048] The coated PCB was placed horizontally in a precision hot air circulating oven and pre-cured at 60-80℃ for 30-60 minutes. In this embodiment, it was pre-cured at a constant temperature of 70℃ for 45 minutes. After pre-curing, the coating was tested with a Shore A hardness tester and the Shore A hardness was 25-35, reaching 60%-80% of the target Shore A hardness of 40 for complete curing. Visual inspection showed that the coating surface was smooth, without cracks or peeling; and there was a noticeable elastic rebound when pressed with a fingertip.

[0049] S4: PCB installed in housing

[0050] The pre-cured PCB is inserted into the PBT housing with the coated side facing upwards. The PCB is positioned by four positioning posts at the bottom of the housing and guide ribs on both sides. After insertion, the gap between the four sides of the PCB and the inner wall of the housing is 1.5~2.0mm, and the upper surface of the coated PCB is about 10mm from the top edge of the housing for potting. At this time, the Hall IC is located on the upper surface of the PCB, and above it is the cavity area inside the housing to be filled with potting material.

[0051] S5: Preheat the entire filling material to a temperature above Tg.

[0052] The potting compound uses a two-component epoxy system. Component A2 is a mixture of bisphenol A type epoxy resin and spherical alumina filler, in which the spherical alumina filler accounts for 60% of the total mass of component A2. Component B2 is methyltetrahydrophthalic anhydride curing agent, with A2:B2=100:80.

[0053] In this composition, bisphenol A epoxy resin serves as the main resin, providing the crosslinking network and adhesion properties. Spherical alumina filler is uniformly dispersed within the bisphenol A epoxy resin to improve the thermal conductivity of the potting compound and reduce its overall coefficient of thermal expansion. Component A2 is prepared by weighing bisphenol A epoxy resin and spherical alumina filler in a specific ratio, then mixing them in a high-speed disperser at 80-100°C for 1-2 hours until the filler is uniformly dispersed.

[0054] When used, after the two components A2 and B2 are mixed, the epoxy groups of the bisphenol A epoxy resin and the anhydride groups of the curing agent undergo a ring-opening crosslinking polymerization reaction under heating conditions to form a three-dimensional network structure and complete the curing process.

[0055] The potting compound was tested using DSC (heating rate 10℃ / min, nitrogen atmosphere) and found to have a Tg of 118℃, a gel point of approximately 105℃, and a rapid curing initiation temperature of approximately 155℃. The potting compound's potting life at 125℃ was tested using the flat knife method and found to be approximately 35 minutes.

[0056] The housing containing the PCB was placed in a programmable temperature-controlled oven and heated from room temperature to a preheating temperature Tp = 125℃ (Tg + 7℃) at a rate of 2~3℃ / min (2.5℃ / min in this embodiment), and held at this temperature for 15~30min (20min in this embodiment). A type K thermocouple was used to confirm that both the housing and the PCB surface reached 125±2℃.

[0057] The technical basis for setting the preheating temperature Tp to Tg+5~10℃ is as follows: When Tp is lower than Tg, the potting compound is still in a glassy state during potting, and the movement of molecular chain segments is frozen. During the shrinkage in the cooling stage, it cannot coordinate with the shell deformation, and therefore cannot effectively establish compressive prestress. When Tp exceeds Tg by too much (such as ΔT>15℃), the potting compound has already begun to undergo a rapid cross-linking reaction before the potting operation is completed. The viscosity rises sharply and the fluidity decreases significantly, affecting the integrity and uniformity of potting and filling. At the same time, an excessively high Tp will also increase the risk of thermal deformation of the shell.

[0058] Experiments have shown that ΔT = 5~10℃ is the optimal window – within this temperature range, the potting compound is in a rubbery state and has a sufficient operating time window, while the shell (PBT, heat distortion temperature 215℃) has no risk of heat deformation at this temperature.

[0059] S6: Filling at preheated temperature

[0060] Maintain the oven temperature at 125℃. Weigh components A2 and B2 at a mass ratio of 100:80, stir for 3 minutes until the color is uniform, then degas in a vacuum degassing chamber at ≤10 mbar for 15 minutes until the bubble escape frequency drops to less than 5 per minute. Slowly inject the degassed potting compound from one side of the shell at a pouring speed of 5~10 mL / min. The potting compound should flow down the inner wall of the shell and fill from the bottom up until it covers the upper surface of the PCB by about 3 mm, reaching the designed fill height mark line. After filling, let it stand for 2~3 minutes to allow the liquid surface to self-level, and check for surface bubbles larger than 1 mm.

[0061] S7: Thermal Insulation and Curing

[0062] A segmented curing process was adopted: after potting, the gel was pre-cured at 125℃ for 2.0h (curing degree approximately 75~80%); then the temperature was increased to 145℃ at 1.5℃ / min and held for 3.0h to complete the final curing. The degree of curing was confirmed to be >98% by measuring the residual exothermic reaction through DSC testing. Segmented curing slowed down the crosslinking reaction in the gel stage, resulted in gradual volume shrinkage, and released the heat of reaction step by step.

[0063] S8: Controlled slow cooling

[0064] After curing, without opening the oven door, the temperature was reduced from 145°C to 30°C at a controlled cooling rate of 0.5~1.5°C / min (1.0°C / min in this embodiment), for a total cooling time of 115 minutes. During the cooling process, the difference in the coefficients of thermal expansion among the shell (CTE approximately 65 ppm / °C), potting compound (CTE approximately 30~50 ppm / °C), and PCB (CTE approximately 14~16 ppm / °C) resulted in gradient shrinkage: the shell (outer layer, with the largest CTE) experienced the largest shrinkage, the potting compound (middle layer, with the second largest CTE) experienced moderate shrinkage, and the PCB (inner layer, with the smallest CTE) experienced the smallest shrinkage. The outer layer shrank more, while the inner layer shrank less, generating a uniform compressive stress within the potting compound, moving from the outside in and from the shell towards the PCB; this is the aforementioned compressive prestress field. When the sensor module experiences temperature rise during subsequent use, the tensile stress generated by the thermal expansion of the potting compound is in the opposite direction to the compressive prestress. The two stresses cancel each other out, thus significantly reducing the effective net stress transmitted to the Hall IC within the operating temperature range. After cooling, the module is removed, and the casing is inspected for cracks and deformation, and the potting compound surface is smooth and free of dents. X-ray inspection shows an internal void ratio of ≤2%.

[0065] S9: Post-processing and Testing

[0066] The following electrical performance tests were performed on the packaged sensor module:

[0067] Zero-position output test: room temperature 25±5℃, zero external current, supply voltage +5.000V, zero-position output Vnull=2.500V, deviation 0mV.

[0068] Linearity test: Apply a nominal current of 100A (accuracy ±0.05%), output 4.500V, nonlinearity 0.12%.

[0069] Full-range temperature drift test: The sensor module was placed in a high and low temperature test chamber and held at each temperature point of -40℃, -20℃, 0℃, 25℃, 50℃, 75℃, 100℃, and 125℃ for 30 minutes. After the sensor module reached thermal equilibrium, the zero-point output voltage Vnull(T) at each temperature point was measured. Using the zero-point output Vnull(25℃) at 25℃ as the reference value, the zero-point drift at each temperature point was calculated. Take all temperature points The maximum value is taken as the maximum temperature drift across the entire temperature range. The measured maximum temperature drift is 7mV, meaning that the zero-point output drift varies from -7mV to +7mV across the entire temperature range.

[0070] Temperature cycling aging test: After 500 cycles, the zero drift was only 1.0mV, the linearity change was 0.04%, and there was no solder joint cracking or potting compound debonding.

[0071] Comparative Example

[0072] The same PCB, Hall IC, housing, and potting compound (from the same batch) as in the example were used. The difference was that steps S2-S3 (without applying the flexible stress isolation coating) were skipped. Since no coating was applied, there was no coating surface on the PCB, and in step S4, the PCB could be installed into the housing in any orientation. The preheating in step S5 was not performed. After the PCB was installed into the housing in step S4, the potting compound, which had been vacuum degassed under the same conditions, was directly injected at room temperature (25±5℃). The product was then cured at 145℃ for 4.0 hours in one continuous cycle (without segmentation). After curing, the oven was powered off, and the product cooled naturally to room temperature with the oven. The test conditions in step S9 were exactly the same as in the example.

[0073] Comparative test results: Maximum temperature drift of ±18mV across the entire temperature range (test temperature points and baselines are the same as above), zero drift of 7.5mV and linearity change of 0.42% after 500 temperature cycles, with localized debonding of the potting compound at the shell interface.

[0074] In the example, the temperature drift decreased from ±18mV in the comparative example to ±7mV (a reduction of approximately 61%), and the zero-point drift after temperature cycling decreased from 7.5mV in the comparative example to 1.0mV (a reduction of approximately 87%). Comparison confirms that, with identical potting compound, housing, PCB, and IC model, a significant reduction in temperature drift and a substantial improvement in temperature cycling reliability can be achieved simply by adding the flexible stress isolation coating in steps S2-S3 and the preheating-controlled cooling in steps S5-S8. This strongly demonstrates the effectiveness of the combined mechanism of local flexible stress isolation and global thermal pre-compression stress offset described in this invention.

[0075] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A Hall sensor packaging process for eliminating packaging stress, characterized in that: Includes the following steps: S1: PCB soldering: Using SMT reflow soldering process, Hall IC and other electronic components are soldered onto the corresponding pads on the PCB, and then allowed to cool naturally to room temperature after soldering; S2: Application of flexible stress isolation coating: Apply a layer of flexible stress isolation coating material to the surface of the Hall IC package and its surrounding area on the PCB that has been soldered. S3: Pre-curing of flexible stress isolation coating: Pre-cur the coated PCB at 60~80℃ for 30~60min to allow the flexible coating to reach initial shape; S4: PCB installation into the housing: The pre-cured PCB is installed and positioned inside the sensor's plastic housing; S5: Preheat the entire shell to a temperature above Tg of the epoxy potting compound: Place the entire shell into a temperature-controlled oven and heat it at 2~3℃ / min to the preheating temperature Tp=Tg+ΔT, where Tg is the glass transition temperature of the epoxy potting compound, ΔT=5~10℃, and maintain the temperature for 15~30min. S6: Potting at preheated temperature: Keep the oven temperature constant at Tp and inject epoxy potting compound into the shell to the filling height; S7: Thermal curing: Complete the full curing of epoxy potting compound under the set segmented curing temperature curve; S8: Controlled slow cooling: After curing, the temperature is slowly reduced from the curing temperature to 25±5℃ at a controlled cooling rate of 0.5~1.5℃ / min.

2. The Hall sensor packaging process for eliminating packaging stress according to claim 1, characterized in that, The flexible stress isolation coating material mentioned in step S2 is a low-modulus electrical insulating material with a Shore A hardness of 30~50 and an elastic modulus in the range of 0.5~5 MPa, and the ratio of its elastic modulus after curing to the elastic modulus after curing of the epoxy potting compound mentioned in step S6 is ≤1 / 100.

3. The Hall sensor packaging process for eliminating packaging stress according to claim 2, characterized in that, The flexible stress isolation coating material is a two-component addition-type silicone gel. Component A1 is the base component, containing vinyl-terminated polydimethylsiloxane and a platinum catalyst. Component B1 is the crosslinking component, containing a hydrogen-containing silicone oil crosslinking agent and an inhibitor. Components A1 and B1 are mixed in a mass ratio of 10:

1.

4. The Hall sensor packaging process for eliminating packaging stress according to claim 2, characterized in that, The flexible stress isolation coating material is one of a single-component condensation-type room temperature vulcanizing silicone rubber, a two-component polyurethane elastomer, or a modified silicone gel.

5. The Hall sensor packaging process for eliminating packaging stress according to claim 1, characterized in that, The coating thickness of the flexible stress isolation coating in step S2 is 1.0 ± 0.1 mm.

6. The Hall sensor packaging process for eliminating packaging stress according to claim 1, characterized in that, Step S2, before applying the flexible stress isolation coating, also includes an ion activation treatment of the soldered PCB: the PCB is placed in the vacuum chamber of a plasma cleaner, high-purity argon gas is introduced, and the PCB is treated for 60 seconds at a working pressure of 50~80 Pa and a radio frequency power of 200W.

7. The Hall sensor packaging process for eliminating packaging stress according to claim 1, characterized in that, The epoxy potting compound described in step S6 is a two-component epoxy system. Its A2 component is a mixture of bisphenol A type epoxy resin and spherical alumina filler, wherein the spherical alumina filler accounts for 60% of the total mass of the A2 component, and the B2 component is methyltetrahydrophthalic anhydride curing agent, with A2:B2=100:

80.

8. The Hall sensor packaging process for eliminating packaging stress according to claim 7, characterized in that, The segmented curing in step S7 includes: first, pre-curing the gel at 125℃ for 2.0h, then raising the temperature to 145℃ at 1.5℃ / min and holding it at that temperature for 3.0h to complete the curing.

9. The Hall sensor packaging process for eliminating packaging stress according to claim 1, characterized in that, After pre-curing in step S3, the Shore A hardness of the flexible stress isolation coating reaches 60% to 80% of its fully cured target value.

Citation Information

Patent Citations

  • Electronic component packaging structure and packaging method

    CN110718509A

  • A PCB chip and its secondary packaging process

    CN110808236B

  • A method for packaging a stacked hall chip

    CN114388692B